Formation of environmental factors in global market and evaluation of outsourcing business activities - Vasiliauskienė, Ligita (Business: Theory and Practice, 2011)
Outsourcing is not only the engine of globalisation but also a new kind of competition. After evaluation of the opportunities and threats of outsourcing, policy of the country should be targeted at the increasing of the competitiveness of the country and the establishement of the new competition rules. Globalisation has more or less significant effects on all participants of global economics. It opens opportunities for companies to obtain different recources for lower prices. One of the ways to manage business more effectively is application of outsourcing. This way of procurement was usually used for obtaining goods (mostly semimanufactures) both from inside and outside of the country. However, recent rapid development of technologies and communications has generated the new way for obtaining high-qualified professionals from different countries and using their outsourcing services.